The Association Between the Integrated Health Post Activity and the Performance of Community Health Workers in Child Growth and Development Care Service in Karanganyar, Central Java - Lidia Ekiq Kurniavie; Pawito Pawito; Bhisma Murti (Journal of Health Policy and Management, 2020)
Background: Active integrated health post is an integrated health post that conducts routine activities every month and conducts additional activities. There are 61.32% active integrated health posts in Indonesia. Early detection of growth and development is one of the tasks of the cadres at the integrated health post. The role of the integrated health post cadre that is not optimal will have direct and indirect effects on children. This study aimed to analyze the effect of the integrated health post activity on cadre performance in children under five in Karanganyar Regency.Subjects and Method: This study used cross sectional design. This study was conducted in the integrated health post in Karanganyar from August-September 2019. There were 200 female college students involved as the sample of the study. They were selected by simple random sampling. The dependent variable was cadre performance of the integrated health post. The independent variables were cadre education, knowledge, attitude, employment status, years of service, training of children under five growth and development, facilities and infrastructure of the integrated health post, community support, and village government support. This study used questionnaires to collect the data. The data were analyzed by multiple logistic regression run on Stata 13.Results: Cadre performance in children under five growth and development in the integrated health post increased with high cadre education (OR=3.04; 95%CI=1.24 to 7.47; p=0.015), cadres who worked at home (OR=3.66; 95%CI=1.57 to 8.50; p=0.003), high knowledge (OR=4.11; 95%CI= 1.79 to 9.42; p=0.001), good attitude (OR=3.31; 95%CI= 1.31 to 8.38; p=0.011), participation in growth and development training by ≥2 times (OR=3.36; 95%CI=1.49 to 7.60; p=0.004), length of service of the cadres ≥10 years (OR=3.21; 95% CI=1.39 to 7.43; p=0.006), complete facilities and infrastructure of the integrated health post (OR=4.17 ; 95%CI=1.74 to 9.99; p=0.001), strong community support (OR=2.99; 95% CI=1.26 to 7.10; p=0.013), and high village government support (OR=2.76; 95% CI=1.17 up to 6.51; p=0.020).Conclusion: Cadre performance in children under five growth and development is affected by cadre education, cadre occupation, cadre knowledge, cadre attitude, training of growth and development, length of service, facilities and infrastructure of the integrated health post, community support, and village government support.Keywords: cadre performance, integrated health post activity, growth and development, children under fiveCorrespondence:Lidia Ekiq Kurniavie. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: ekiqlkv@gmail.com. Mobile: +6285852540575.Journal of Health Policy and Management (2019), 5(1): 48-60https://doi.org/10.26911/thejhpm.2020.05.01.05